Balanced nutrition in elementary school children - Tala, Zaimah Z; Wali, Syah Mirsya; Darmajaya, Ridha; Daulay, Milahayati (Talenta Publisher, 2019)
Childhood is the critical age that determine the quality of children’s future nutritional status and their growth and development physically and mentally. Nutritional status is influenced by many things, such as nutrition intake, motor and psychomotor activity, and infectious diseases. The purpose of this community service is to increase the knowledge of teachers and students in balanced nutrition intake and the applicable methode to choose and to consume balanced nutrition so we can achieve the perfect nutritional status. The community service is held in June-December 2019 by doing 1)socialization about balanced nutrition in childhood, 2)explanation of how to calculate Body Mass Index (BMI) per age, 3) demonstration of how to determine nutritional status by calculating BMI per age 4) classify the nutritional status that obtained from the calculation of BMI per age. The result of the community service is the average students have good nutritional status, but some students are obese which means bad nutritional status. The Evaluation result is the increase of knowledge and skills of students and teachers in calculating BMI and determining children’s nutritional status to increase children’s quality of growth and development.